Sensors and “The internet of biochemical things” - Florea, Larisa; Diamond, Dermot (Frontiers in Sensors, 2022)
In this perspective article, we consider the pathway biochemical sensing will take as the huge businesses underpinning Big Data and the Internet of Things seek new layers of highly valuable information to integrate into our increasingly digitised world. Up to now, the complexity of biochemical sensing has limited its inclusion in a manner similar to more reliable and lower cost technologies based on physical transducers. At its core, this complexity arises from the fundamental need for biochemical sensors to interact intimately at the molecular level with one or more specific components (analytes) in samples that are often highly complex and hostile to the sensors. This limits the functional lifetime of biochemical sensors to at best days or weeks or most commonly single use, making long-term embedded use-models developed for Internet of Things applications beyond reach. Nevertheless, even single use sensors can lead to “big data”, if used in large enough scale (e.g., COVID-19 diagnostics), and progress in continuous is beginning to make headway towards longer-term use models in health and environmental monitoring. New concepts exploiting advanced materials and biomimetic concepts offer opportunities to further extend the lifetime of biochemical sensing devices.